Las TIC y su influencia en el aprendizaje de los estudiantes en el bachillerato de la Unidad Educativa Emigdio Esparza Moreno - Figueroa Montesdeoca, Juliana Sthephania (2022)
In short, we can indicate how important our case study is going to be within our Emigdio Esparza Moreno Educational Unit to promote the proper use of ICT, which will benefit the Emigdio Esparza Moreno Educational Unit and its components, since the insertion of new information and communication technologies in the educational field, according to Daros, will have an impact on the cognitive development of students, favoring the student's learning process. The knowledge society is widely satisfied by the large amount of information found through ICT, which helps the individual to build their own knowledge system and in turn to share, transform, modify or reaffirm it in virtual communities. . In addition to creating new information and communication strategies, ICTs renew the means of communication and search for information, for example, the exposure of virtual libraries has favored the investigation of many students who, without moving, can access countless books to their formation. Technology has gained important ground in the educational field, for which we must seek advantages of its use, improve communication between the different agents of the teaching-learning process, or rapid access to information and the possibility of interacting with information. Innovation, teachers can apply new teaching-learning methods.